Aquaculture and poverty alleviation in Ben Tre Province, Vietnam. Issue 1 (2nd January 2016) - Nguyen, Kim Anh Thi; Jolly, Curtis M.; Bui, Chuong N.P.T.; Le, Trang T. H.
ABSTRACT: Research results on the effects of aquaculture on poverty alleviation have been mixed. We use Tobit, simulation models and cross sectional survey data of 285 households, in Ben Tre Province, Vietnam, to evaluate the effects of aquaculture involvement on poverty, measured using per capita consumption of less than $1.25 USD, $1.50, and $2.00 per day. The results show for per capita consumption of less than $1.25 per day that households' aquaculture participation or productivity had no or little effect on the living standard. For income levels above $1.25 per capita per day aquaculture participation or productivity influenced the standard of living.